Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2012
DOI: 10.3758/s13421-012-0252-y
|View full text |Cite
|
Sign up to set email alerts
|

Idealness and similarity in goal-derived categories: A computational examination

Abstract: The finding that the typicality gradient in goalderived categories is mainly driven by ideals rather than by exemplar similarity has stood uncontested for nearly three decades. Due to the rather rigid earlier implementations of similarity, a key question has remained-that is, whether a more flexible approach to similarity would alter the conclusions. In the present study, we evaluated whether a similarity-based approach that allows for dimensional weighting could account for findings in goal-derived categories… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 59 publications
0
8
0
Order By: Relevance
“…Drawing on evidence that categories are defined by goal‐derived or ‘ad hoc’ elaborations of associations between traits (Barsalou, , ) and that they are constructed ‘online’ by relying on pre‐existing knowledge structures (Lakoff, ; Murphy, ), we argue that the categorical prototype for TGSs and other network‐based forms does not represent a summary representation of comparable members. Rather, TGSs are legitimized as a category through intuiters' appraisals of whether affiliates correspond to an abstract ‘ideal’, which describes sets of traits that intuiters regard as desirable (Barsalou, ; Burnett et al., ; Lakoff, ; Voorspoels et al., ).…”
Section: Legitimacy Spillovers: How Network Differ From Classesmentioning
confidence: 99%
“…Drawing on evidence that categories are defined by goal‐derived or ‘ad hoc’ elaborations of associations between traits (Barsalou, , ) and that they are constructed ‘online’ by relying on pre‐existing knowledge structures (Lakoff, ; Murphy, ), we argue that the categorical prototype for TGSs and other network‐based forms does not represent a summary representation of comparable members. Rather, TGSs are legitimized as a category through intuiters' appraisals of whether affiliates correspond to an abstract ‘ideal’, which describes sets of traits that intuiters regard as desirable (Barsalou, ; Burnett et al., ; Lakoff, ; Voorspoels et al., ).…”
Section: Legitimacy Spillovers: How Network Differ From Classesmentioning
confidence: 99%
“…- -----------------------------------------------INSERT TABLE 2 ABOUT HERE - -----------------------------------------------Much subsequent work, using more sophisticated and ambitious methods, has confirmed these initial results (e.g., Borkenau, 1990;Chaplin, John, & Goldberg, 1988;Loken & Ward, 1990;Lynch, Coley, & Medin, 2000;Read, Jones, & Miller, 1990;Voorspoels, Storms, & Vanpaemel, 2013;Voorspoels, Vanpaemel, & Storms, 2010. Perhaps most surprisingly, ideals tend to emerge as not only important determinants of typicality, but often as the most important determinants, even for taxonomic categories.…”
Section: Contrasting Central Tendency Ideals and Frequency Of Instantiationmentioning
confidence: 79%
“…The lack of a stability difference might be an indication that the ad hoc categories we selected should be considered goal-derived categories: ad hoc categories that have become well-established in memory, for example, through frequent use (Barsalou, 1985). The observation that one and the same individual may use different criteria for recruiting items that fulfill the category’s goal, would then be an indication that people sometimes entertain competing goals—such as traveling comfortably or fast between Brussels and London—the prominence of which might change from one occasion to the next (see also Voorspoels, Storms, & Vanpaemel, 2013, who showed that individuals can provide multiple ideal characteristics of goal-derived categories).…”
Section: Discussionmentioning
confidence: 99%